Solitary Neurofibroma of the Frontal Sinus - Sudhir B. Sharma; Paul Hong (Case Reports in Otolaryngology)
Isolated or solitary neurofibromas of the paranasal sinuses are rare. Mostly, they involve the maxillary sinus and so far, a solitary neurofibroma of the frontal sinus has never been reported in the literature. We present a case of frontal sinus neurofibroma treated successfully with surgical excision. A 28-year-old male presented with forehead swelling and computed tomography images revealed a tumor involving the left frontal sinus. Histopathological examination showed the tumor to be a neurofibroma. We discuss the clinical and pathological characteristics of neurofibroma arising in the nasal cavity and paranasal sinuses.